Social Representations that Adolescents from Guadalajara, Mexico Have About Human Influenza - Torres-López, Teresa Margarita (2017)
The aim was to analyze social representations (SR) that adolescents from Guadalajara, Mexico have about human influenza, during the epidemic of 2009 and in early 2016 in the presence of an influenza outbreak. Free listings associative technique was applied to 112 adolescents, in the interest of knowing the RS structure by a prototypical analysis and the thematic content by procesual analysis. The findings show that influenza SR in 2009 was on construction process. It is contradictory because they underline its danger, and at the same time they point the influenza as a lie or exaggeration. In 2016 it seems to have redefined around symptoms, care and possible consequences.